Population features of prevalence and clinical-diagnostic role of NOD2 gene polymorphisms associated with Crohn’s disease - D. A. Kuznetsova; M. V. Merzlyakov; G. V. Vavin; A. S. Razumov; V. L. Emanue (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To discuss features of prevalence and the clinicodiagnostic role of R702W, G908R and 3020insC NOD2 gene polymorphisms associated to Crohn's disease (CD) in various populations and regions of the world. Key points. It is established that there are significant differences in prevalence and clinical manifestations of R702W, G908R and 3020insC polymorphisms of NOD2 gene associated to CD in different countries, as well as in different regions of the same country and in representatives of different ethnic groups enhabiting different regions. Some populations are characterized by high prevalence of the above-mentioned polymorphisms in the absence of CD association, the others are characterized by low prevalence while the association to CD is present, in the third the absence of associations to the Crohn's disease risk is combined to integration of polymorphisms to specific features of the course of disease, treatment efficacy and surgery rate. Conclusion. According to literature data analysis it is possible to conclude that there are clear populationrelated features of the prevalence, clinical and diagnostic role of NOD2 genetic polymorphism associated to Crohn's disease that requires development of the international data bank of all genetic nucleotide polymorphisms associated to various stages of CD pathogenesis in different countries and populations. It will allow not only to increase efficacy of early diagnosis and the CD risk prognosis, but to define environmental factors affecting clinical utilization of genetic factors that is a premise for development of pathogenic justified management algorithm encompassing both populationbased and regional factors.